MAIT cells are enriched in portal tracts and respond to biliary epithelial cells presenting bacterial ligands during liver inflammation - Jeffery, H; Van Wilgenburg, B; Stirling, K; Parekh, K; Roberts, S; Kurioka, A; Hunter, S; Adams, D; Klenerman, P; Oo, Y (Wiley, 2015)
Mucosal-Associated Invariant T (MAIT) cells are unconventional T-cells characterised by the invariant T-cell antigen receptor α-chain, Vα7.2, high expression of CD161 and restriction by the MHC class 1-related molecule, MR1. They are important for antibacterial immunity at mucosal sites; however, their role in the pathogenesis of hepatic inflammation remains unclear. Here we investigated the frequency, phenotype, localisation and function of liver infiltrating (LI) MAIT cells.